2005
DOI: 10.1055/s-2005-871281
|View full text |Cite
|
Sign up to set email alerts
|

8-NH2-Boldine, an Antagonist of α1Aand α1BAdrenoceptors without Affinity for the α1DSubtype: Structural Requirements for Aporphines at α1-Adrenoceptor Subtypes

Abstract: Structure-activity analysis of 21 aporphine derivatives was performed by examining their affinities for cloned human alpha (1A), alpha (1B) and alpha (1D) adrenoceptors (AR) using membranes prepared from rat-1 fibroblasts stably expressing each alpha (1)-AR subtype. All the compounds tested competed for [ (125)I]-HEAT binding with steep and monophasic curves. The most interesting compound was 8-NH (2)-boldine, which retains the selective affinity for alpha(1A)-AR (pKi = 6.37 +/- 0.21) vs. alpha(1B)-AR (pKi = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…This pattern of behaviour has also been observed in studies carried out in our laboratory on the individual enantiomers of roemerine ( 2a ) and nuciferine ( 3a ) . Similarly, both enantiomers of these three compounds, as well as apomorphine ( 4a ) and N ‐n‐propylnorapomorphine ( 4b ), have been found to antagonize α 1 receptors . We therefore decided to investigate whether the structurally related compounds, isolaureline ( 2b ), dicentrine ( 2c ) and glaucine ( 3b ) follow the same pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of behaviour has also been observed in studies carried out in our laboratory on the individual enantiomers of roemerine ( 2a ) and nuciferine ( 3a ) . Similarly, both enantiomers of these three compounds, as well as apomorphine ( 4a ) and N ‐n‐propylnorapomorphine ( 4b ), have been found to antagonize α 1 receptors . We therefore decided to investigate whether the structurally related compounds, isolaureline ( 2b ), dicentrine ( 2c ) and glaucine ( 3b ) follow the same pattern.…”
Section: Introductionmentioning
confidence: 99%
“…26 Others have documented the affinity trends of aporphines at the α 1A receptor, but no study has done so with nantenine as the lead. 12 One prior study has investigated the structure-affinity relationships of nantenine at α 1 receptors. 27 Here it was reported that replacement of the C1 methoxy group with a hydroxyl group gave improved α 1 affinity.…”
Section: Introductionmentioning
confidence: 99%
“…18 As central nervous system (CNS) receptor ligands, aporphines have been found to possess high affinity for a number of dopamine receptors (predominantly D 1 and D 2 ), 912 serotonin (5-HT) receptors 1315 and α-adrenergic receptors. 6,16 Furthermore, aporphines are known with both agonist and antagonist activity at neuroreceptor sites. The continued exploration of the aporphine template over the last few decades has been driven to some extent by the opportunity/promise for discovery of new ligands with high potency and selectivity for subtypes of the above-mentioned receptors.…”
mentioning
confidence: 99%